Perbandingan Jumlah Sel Osteoblas pada Penyembuhan Luka Antara Penggunaan Kitosan Gel 1% dan 2% - Sularsih Sularsih; Soeprijanto Soeprijanto (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
The use of chitosan in medical fields known as biomaterial nowdays can be used in dental clinical application. Chitosan is obtained by N-acetylating chitin and it is a biodegradable natural biopolymer that can enhance bone healing. The aim of this study was to compare account the rate of osteoblast cells on bone healing process of dental extraction in Rattus norvegicus for 7 and 14 days. Rattus nornegicus strain wistar male, aged 8-16 weeks, divided into 3 treatment groups namely group 1 which given chitosan gel 1%, group II which given chitosan gel 2 % and group III as control which were not given chitosan gel. Chitosan were applied into the socket of dental extraction. Rat was decaputated 7 and 14 days after chitosan application and the jaw in the treated regions and control group were cut for histopatological to observe the number of osteoblast cells. Data were analyzed using t test. The result showed no significant differences in osteoblast cells number between the use chitosan gel 1 and 2 % in 7 and 14 days observation (p<0,05). There was not different number of osteoblast cells with application between chitosan gel 1 % and 2 %. It can be concluded that chitosan gel 1 and 2 % has ability to enhance the bone healing process in post extraction socket of Rattus norvegicus.